Saporin-conjugated tetramers identify efficacious anti-HIV CD8+ T-cell specificities. - Leitman, E; Palmer, C; Buus, S; Chen, F; Riddell, L; Sims, S; Klenerman, P; Sáez-Cirión, A; Walker, B; Hess, P; Altfeld, M; Matthews, P; et al. (Public Library of Science, 2017)
Antigen-specific T-cells are highly variable, spanning potent antiviral efficacy and damaging auto-reactivity. In virus infections, identifying the most efficacious responses is critical to vaccine design. However, current methods depend on indirect measures or on ex vivo expanded CTL clones. We here describe a novel application of cytotoxic saporin-conjugated tetramers to kill antigen-specific T-cells without significant off-target effects. The relative efficacy of distinct antiviral CD8+ T-cell specificity can be directly assessed via antigen-specific CD8+ T-cell depletion. The utility of these reagents is demonstrated here in identifying the CD8+ T-cell specificity most effective in preventing HIV progression in HIV-infected HLA-B*27-positive immune controllers.